ACCRUAL OF CAUSE OF ACTION FOR THE OPERATION OF LIMITATION PERIOD IN EMPLOYMENT MATTERS IN NIGERIA: DR. FABUNMI V. UNIVERSITY OF IBADAN & ANOR: LESSONS FROM GHANA AND UGANDA (UUM Journal of Legal Studies, 2025)
Crystalisation of the right to seek legal redress is known as accrual of cause of action, which is when all the factual circumstances that would justify and enable an aggrieved party to seek legal redress have occurred and to his/her knowledge. However, the Nigerian Court of Appeal in Dr. Fabunmi v. University of Ibadan & Anor. held that the cause of action for dismissal of an employee arises from the date the letter of dismissal was dated, not when it was delivered or received by the dismissed employee. This paper adopts doctrinal and comparative methods, relying on primary and secondary data to examine the impact of this decision on the security of employment in Nigeria and its sustainability. It raises the question of whether it is legally practicable for an employee whose termination has not been communicated to by the employer to take steps to challenge the same in court. The paper argues that this decision is capable of enabling employers to perpetuate fraud and unfair labour practices in the course of termination of employment, since it holds that the cause of action accrues based on the date the termination letter is written, rather than the date it is delivered or received. It found that the court failed to take cognisance of the fact that countenancing when the letter of dismissal/termination is dated as opposed to when it was delivered/received by the concerned employee is encouraging concealment by employers to ensure that before employees would take steps to challenge dismissal/termination of their employment, limitation period would have set in. Also, the decision is diametrically opposed to the principle that the law does not require the doing of the impossible, as a person cannot be expected to seek legal redress over a wrong unknown to him/her. Giving the prevalence of unemployment in Nigeria, the decision is an unwelcomed development; while it is noted that by virtue of Section 253 of the Constitution of the Federal Republic of Nigeria 1999, the decision of the Court of Appeal on civil matters from the National Industrial Court is final, therefore, there cannot be further appeal to the Supreme Court. To address the problem created by Fabunmi’s case, it is recommended that the Court of Appeal, in subsequent cases, should jettison the position taken in this case so that it will not be a precedent.